A Comparative Efficacy of Low-Dose Combined Oral Contraceptives Containing Desogestrel and Drospirenone in Premenstrual Symptoms - Jirath Wichianpitaya; Surasak Taneepanichskul (Obstetrics and Gynecology International)
Objective. To compare the efficacy of low-dose COC containing desogestrel (DSG) with drospirenone (DRSP) in the changes of premenstrual symptoms. Methods. In an open-label randomized controlled trial, 90 women with premenstrual syndrome who required COC were randomly recruited and allocated equally to receive either 6 cycles of 20 micrograms ethinyl estradiol (EE)/150 micrograms DSG (DSG group) or 20 micrograms EE/3 mg DRSP (DRSP group) in 24/4 extended regimen. Analysis of covariance and repeated analysis of variance were used to determine the difference of mean Women's Health Assessment Questionnaire (WHAQ) scores changes between groups, within group, and in premenstrual, menstrual, and postmenstrual phases. Results. Baseline characteristics and WHAQ scores were comparable. At the ends of the 3rd and the 6th cycles, mean WHAQ scores of all the 3 phases in DRSP group showed significant reduction and were significantly lower than those in DSG group. DSG group showed significant reduction in both premenstrual and menstrual phases after the 6th cycle. Adverse effects were comparable in both groups. In conclusion, low-dose COC containing either DSG or DRSP reduced premenstrual symptoms, but the latter showed greater efficacy and earlier reduction.